Recursive Models of Dynamic Linear Economics - Hansen, Lars Peter; Sargent, Thomas J. (Princeton and Oxford Princeton University Press, 2014)
A common set of mathematical tools underlies dynamic optimization, dynamic estimation, and filtering. In Recursive Models of Dynamic Linear Economies, Lars Peter Hansen and Thomas Sargent use these tools to create a class of econometrically tractable models of prices and quantities. They present examples from microeconomics, macroeconomics, and asset pricing. The models are cast in terms of a representative consumer. While Hansen and Sargent demonstrate the analytical benefits acquired when an analysis with a representative consumer is possible, they also characterize the restrictiveness of assumptions under which a representative household justifies a purely aggregative analysis.
Keywords: Economics--Mathematical models; Society & Social Sciences; Psychology